What’s on the menu? A qualitative study on the views of care home staff and residents on nutritional practices and implications for oral health - Aditi Mondkar; Maritess Murdoch; Jennifer E. Gallagher; Rakhee Patel (BDJ Open)
Abstract Introduction People living in nursing or residential homes are at an increased risk of having or developing oral and dental diseases. This is due to contributing factors such as comorbidities and polypharmacy coupled with poor manual dexterity and lack of disease prevention and access to care. These risk factors combined with frequent and high sugar consumption increases risk of developing dental decay. Care home residents are a diverse population from different backgrounds. Little is known about decision making around nutrition in care settings and nutritional practices of older people in care homes, including the choices and challenges. The purpose of this study was therefore, to understand care home landscape and resident experiences. Materials and methods Semi-structured interviews were conducted with participants including residents, care home managers, carers and kitchen staff. Interviews were held face-to-face, recorded and transcribed and the findings were analysed using a thematic approach. Results A total of 17 participants across 4 care homes in one outer London borough took part in this study, with findings relating to both nutrition and oral health. Resident food preferences were collected upon admission into the home, including information on the incoming resident’s lifestyle, routine and choices. Staff tried to maintain these where possible and accommodate to resident choices when possible. Opportunities for wider food choice was dependent on the residents’ ability and willingness to request alternatives, their financial freedom to purchase their own foods, mobility to access food outside of the care home setting and food bought in by family and friends. This was compounded by residents being prescribed high calorie, high sugar meal supplemented for weight management. Participants reported that the structured routine revolved around meals and activities. Most care staff reported that an alternative healthy option was offered at mealtimes, but this was not the case in all homes. Care staff faced challenges managing weight of residents who had appetite loss and tried to accommodate and make provisions for those with these experiences and were aware of how to raise concerns. There was variation in mandatory training expectations, with no integration of oral health and nutrition. Discussion The findings provided valuable insight into the disparities between and within homes and highlights the challenges in this complex group with regards to nutritional choices. It is vital that a range of food options are in place to protect residents’ rights to choose what they wish to eat, whilst offering healthy options and all care staff are educated on offering balanced, nutritious meal and snack options. By offering a range of foods, the healthier choice can be the easier choice.